Autonomic modulation and association with the performance in a jump test in university Colombian players of rugby seven - Tafur Tascón, L. J.; Cabrera Hernandez, M. A.; Neisa Herrera, L. F.; García-Corzo, S. A.; Povea Combariza, C. H.; Tejada Rojas, C. X. (Journal of Human Sport & Exercise, 2019)
It has been observed that training influences modulation of autonomic activity and it can be represented in Heart Rate Variability (HRV). Evaluation of HRV can be useful to obtain information about the internal load to which an individual is being subjected, in order to adjust training loads, either with the aim of increasing sports performance or to prescribe an adequate load to improve specific qualities for the sport. Therefore, the purpose of this study was to evaluate the behaviour of autonomic modulation and its association with performance in a jump test, in university players of Rugby Seven. 11 men who belonged to the university team (age 23.63 ± 2.15 years; weight 84.43 ± 10.44 kg; height 1.80 ± 0.04 m), national champion of Colombia in the year 2016 of Rugby Seven, were volunteers for the research. Abalakov jump, CMJ, SJ and DJ were evaluated. We evaluated the behaviour of the autonomic modulation, in controlled resting situation, controlled ventilation, orthostatism, exercise and recovery. Main result of this study was evidence that sympathetic modulation can be reflected in the development of force to execute a jump; because association found between the low frequency component of heart rate variability (2238.364 ± 1381.531 ms2/Hz) and performance in DJ (22.3 ± 3.66 cm) (r=0.65, p=0.029).